Endoscopic guided PCNL in the prone split-leg position versus supine PCNL: a comparative analysis stratified by Guy's stone score - Batagello, Carlos A; Barone Dos Santos, Hugo D; Nguyen, Andrew H; Alshara, Luay; Li, Jianbo; Marchini, Giovanni Scala; Vicentini, Fabio C; Torricelli, Fabio César Miranda; Danilovic, Alexandre; Pereira, Jessica Goulart; Rose, Emily; Srougi, Miguel; et al. (Canadian journal of urology, 2019)
The optimal patient positioning for percutaneous nephrolithotomy (PCNL) based on the complexity of stone burden is not yet defined. Thus, we aimed to evaluate the intraoperative parameters, effectiveness and complications of patients undergoing PCNL between the endoscopic-guided prone split-leg PCNL (ePSL) and the supine PCNL by stratifying patients according to Guy's stone score (GSS). A retrospective chart review was conducted of patients undergoing PCNL at two high-volume tertiary referral centers. At one center, patients underwent PCNL using the ePSL technique, while at the second center, patients underwent PCNL in supine. Patient demographics and stone characteristics, operative details, complications and effectiveness were compared between groups. The impact of obesity was also investigated. Of 830 subjects, a total of 449 (54%) underwent PCNL in ePSL and 381 (46%) in supine. The ePSL group had a greater mean age and body mass index. No statistical differences were found in gender, serum chemistry and Charlson comorbidity index. After stratifying patients by GSS, the differences in baseline stone burden between PSL and supine lost significance and both groups could be compared. Complications were not statistically different between both groups. Univariate analysis demonstrated that multiple tracts and lower pole access were more prevalent in supine. In addition, for GSS1-3, ePSL was correlated with reduced operative time, radiation exposure, length of hospital stay and need for secondary procedure. Multivariate analysis correlated ePSL with lower radiation exposure and need for secondary procedures (p = 0.01). In comparison to the whole trial population, the same tendencies were appreciated for obese cohort. This is the first report focusing on the performance differences between ePSL and supine PCNL stratified by GSS. Both techniques are safe, with a low rate of complications. For GSS1-3, ePSL reduces radiation exposure and requires less need for both multiple access and secondary procedure.